Risk Identification and Control in Oman’s Construction Industry: A Systematic Review and Conceptual Framework - Salim, ‪Rashid; Norhisham, Shuhairy; Zakwan, Muhammad; Al-Shukaili, Azan; Al-Qassabi, Masoud (PT Mattawang Mediatama Solution, 2026)
The construction industry in Oman faces significant risks that influence cost, time, and overall project performance. Although risk management has been widely studied globally, research focusing specifically on Oman and the Middle Eastern context remains limited. This study manages this gap by conducting a systematic literature review on risk identification and control strategies in construction projects. Eligible studies were selected by using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. SCOPUS and ScienceDirect were selected as the leading journal databases. A total of 33 articles were selected for further analysis through this procedure. The review synthesises findings from recent studies, highlighting critical risk identification and classification, including financial, environmental, operational, logistical, regulatory, legal, health and safety, and market risks, as well as strategies for mitigating them. Several recommendations were also suggested to provide the essential knowledge and information for future research. Based on the insights gained, a conceptual framework is proposed to guide risk control practices in Oman’s construction industry.